(untitled) (UNED Research Journal, 2019)
Widespread thinning and retreat of ice shelves along the margins of Antarctica provide a unique opportunity to understand the evolution of Antarctic coastal ecosystems and the consequences of abrupt global change in high latitudes. As dark environments isolated from the atmosphere, the under-ice-shelf ecosystems remain mostly unknown. After ice shelf breakup there is an opportunity to study the evolution of the coastal ecosystem exposed to the atmosphere after millennia. One of the more active regions is the Larsen Ice Shelf, on the NW of the Weddell Sea. After the ice shelf breakup, phytoplankton grow in the presence of light; primary production rates observed are amongst the highest in Antarctica. Zooplanktonic and benthic communities in the marine food web can feed on this newly synthesized carbon. In this way, regions previously unproductive are now able to absorb carbon dioxide and contribute to its absorption by the ocean.